The Contribution of Islamic Boarding Schools in Reducing Ethnocentrism - M. Taufan Khasani; Umi Zuhdiyah (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research is motivated by the phenomenon of ethnocentrism at the Al-Azhar Center Baturaja Islamic Boarding School. The purpose of this research is to find out the forms of ethnocentrism, efforts to reduce it, and the factors that make ethnocentrism persist. Mudir and all Ustadz have made every effort to reduce ethnocentrism. However, inter-ethnic student conflicts still occur due to ethnocentrism. The research approach, qualitative descriptive type, with informant selection techniques, purposive sampling. Collecting data by participatory observation, in-depth interviews, and documentation studies. The literature study was analyzed using Miles & Huberman's data analysis techniques (data reduction, data display, and conclusion drawing). The results of the study show that efforts to reduce ethnocentrism in PP. Al-Azhar Center Baturaja, has been carried out to the fullest, but the ethnocentrism of language persists. Factors that cause ethnocentrism from outside the school environment are very strong.